THE IMPACT OF DOWRY SYSTEM IN THE CHRISTIAN COMMUNITIES: Report of the Field Study Conducted in the States of Andhra Pradesh, Kerala And Tamil Nadu - Kumar, A. Vimal; Vannekuty, Bala Kiran; Gone, Joseph Thambi; Sharma, M.R.; Kochuthara, Shaji George (Asian Horizons, 2013)
Students of Licentiate in Moral Theology at Dharmaram Vidya Kshetram (DVK) conduct a field study every year at the end of the first of their course. The topic for the field study for the academic year 2012-2013 was “The Impact of Dowry System in the Christian Communities: A Study Conducted in the States of Andhra Pradesh, Kerala and Tamil Nadu.” After due preparation, the study was conducted during the months of April and May, 2013 and the report was presented in July 2013. The study was guided by Prof. M.R. Sharma, a social scientist and Shaji George Kochuthara, director of the Moral Theology Licentiate programme at DVK. A. Vimal Kumar, MMI, Bala Kiran Vannekuty and Jose